Feasibility study on the technical and economic performance grid-connected PV system for designated rooftops in UTHM - Mohamad Ali, Mohamad Fakrie (2021)
This project is about the feasibility study on the technical and economic performance grid-connected photovoltaic (PV) system for designated rooftops in UTHM. Analysis of electricity consumption data and electricity bill data of UTHM campus show that the monthly electricity usage in UTHM campus is very high and expensive. The main purpose of this project is to reduce the annual electricity consumption and electricity bill of UTHM with Net Energy Metering (NEM) scheme. Therefore, a grid-connected PV system is designed at Dewan Sultan Ibrahim (DSI), Tunku Tun Aminah Library (TTAL), Fakulti Kejuruteraan Awam dan Alam Bina (FKAAS) and F2 buildings using three types of PV modules which are mono-crystalline silicon, poly-crystalline silicon and Cadmium Telluride (CdTe). The technical of these three PV modules are modeled, simulated and estimated using Helioscope software with the capacity of 2,166.40 kWp, 2,046.20 kWp and 1,845 kWp with the total rooftop area of 190,302.9 ft². Economic analysis is conducted on the chosen three installed PV modules using RETScreen software. The performance analysis showed that mono-crystalline silicon, poly-crystalline silicon and thin film (CdTe) systems are exported 2,332,327.40 kWh, 2,182,727.90 kWh and 2,066,755.40 kWh respectively to the grid annually. Technically, the mono-Si system has emerged as the best PV module in terms of performance ratio which 74.03% and followed closely by poly-si and CdTe by 73.73% and 73.70%. In economic aspect, mono-si monopolized in all aspects compared to the other two systems which 2,332,327.40 kWh of Net PV generated energy, 4.4% CO₂ reduction, 9.3 years of payback period considering 21 years of the contractual period and RM 4,932,274.58 for 11.7 years after payback period. As a result, the mono-Si is the best PV module and the UTHM campus annual electricity bill have reduced by 3.6% which is about RM 421,561.93 per year.